Factors that influence lecturers’ internet use in teaching: an exploratory study of Gauteng public technical and vocational education and training (TVET) colleges - Mthembu, Vusumuzi (My University, 2018)
The use of Internet is increasingly permeating across spheres of human activity, including the sphere of education and teaching. It is therefore important to locate the Internet as core medium for instruction at colleges to enhance the teaching and learning experience and better prepare students for the demands of the knowledge society that is largely driven by the Internet. The purpose of this mixed-method research is to explore factors that influence lecturer Internet use in teaching at public technical and vocational education and training (TVET) colleges in Gauteng. The study investigates the forms (what the Internet is used for) and the characteristics (how it is used) in teaching. Furthermore, the study investigates the extent of lecturer Internet use in teaching at the TVET colleges. Literature shows that factors that Influence the Internet use in teaching at TVET colleges are multi-dimensional in nature. For this reason the research appropriate a combination of theoretical artefacts that include adapted TPACK framework, blended learning institutional development model, technology adoption model and institutional level factor theoretical framework to explore these factors. The outcome of the research shows that Internet use in teaching public colleges in Gauteng is influenced by a confluence of factors that can be classified as lecturer level, institutional and macro-policy factors. The research further reveal that the use of the Internet in teaching at public TVET colleges is opportunistic and is at an embryonic stage
A research report submitted to the Faculty of Humanities, University of the Witwatersrand in partial fulfillment of Master of Arts in ICT Policy and Regulations March 2018
Keywords: Teaching--Computer network resources; Internet in education; Education|--Computer network resources